Rethinking the Secular: Science, Technology, and Religion Today - Szerszynski, Bronislaw (Zygon, 2005)
Abstract. Contemporary tensions between science and religion cannot simply be seen as a manifestation of an eternal tension between reason and revelation. Instead, the modern secular, including science and technology, needs to be seen as a distinctive historical phenomenon, produced and still radically conditioned by the religious history of the West. Clashes between religion and science thus ought to be seen fundamentally as part of a dialogue that is internal to Western religious history. While largely agreeing with Caiazza's account of the “magical” understanding of technology, I suggest that this needs to be seen as part of a more fundamental drift in religion and culture away from canonical meanings to more “indexical,” pragmatic ones—but also that technology is still inflected by soteriological meanings that were coded into modern technology at its very inception in the early modern period. I conclude by arguing that a recognition of science and technology's grounding in Western religious history can make possible a more fundamental encounter with religion.